2001
DOI: 10.1159/000045909
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Renal Tubular Cells in Shiga-Toxin-Mediated Hemolytic Uremic Syndrome

Abstract: In order to clarify the mechanism of unusual renal tubular dysfunction seen in a child with Shiga toxin (Stx)-mediated hemolytic uremic syndrome (HUS), we studied the renal biopsy specimens for Stx binding and apoptosis of renal tubular cells. A 7-year-old boy with Stx-2-mediated HUS demonstrated extensive renal tubular damage characterized by nonoliguric acute renal failure, increased urinary tubular enzymes and defective urine-concentrating capacity. His renal biopsy specimens were analyzed for Stx binding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 8 publications
1
36
0
Order By: Relevance
“…In vitro experiments have revealed that Stx1 induces cell death in renal tubular epithelial cells through protein synthesis inhibition and apoptosis (Karpman et al, 1998;Kiyokawa et al, 1998;Taguchi et al, 1998;Williams et al, 1999). Several clinical studies have indicated the involvement of renal tubular damage during the course of HUS (Kaneko et al, 2001;Takeda et al, 1993). The appearance of apoptotic cells in the renal tubules of the kidney in HUS patients, accompanied by STEC infection, further indicates that renal tubular injury does occur in the kidneys of HUS patients (Karpman et al, 1998;Taguchi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have revealed that Stx1 induces cell death in renal tubular epithelial cells through protein synthesis inhibition and apoptosis (Karpman et al, 1998;Kiyokawa et al, 1998;Taguchi et al, 1998;Williams et al, 1999). Several clinical studies have indicated the involvement of renal tubular damage during the course of HUS (Kaneko et al, 2001;Takeda et al, 1993). The appearance of apoptotic cells in the renal tubules of the kidney in HUS patients, accompanied by STEC infection, further indicates that renal tubular injury does occur in the kidneys of HUS patients (Karpman et al, 1998;Taguchi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, genes encoding the virulence determinants and their expression regulator have been used to characterize numerous bacteria. A molecular test based on the detection of shiga-like toxin (verotoxin type II), femA (cytoplasmic protein), toxR (trans-membrane DNA binding protein), iap (invasive associative protein), and invA (invasion protein A) genes has been applied for identification of E. coli O157:H7 (Jinneman et al, 2003;Kaneko et al, 2001;Karpman et al, 1998;Schmidt et al, 1995;Wang et al, 2002), Staphylococcus aureus (Mehrotra et al, 2000), Vibrio parahaemolyticus (Karpman et al, 1998;Cabrera-Garcia et al, 2004), Listeria monocytogenes (Bubert et al, 1992;Bubert et al, 1999;Volokhov et al, 2002), and Salmonella spp. (Chiu et al, 1996).…”
mentioning
confidence: 99%
“…Because the IECs are the first line in contact with Stx in a host, the interaction of Stx with epithelium may be a pivotal role in HUS 3) through induction of apoptosis in vivo and in vitro studies. [7][8][9][10] Apoptosis of IECs could destroy the barriers in host lumen and permit Stx to enter the bloodstream and attack the central nervous and/or renal systems. 5,11) In many cells, Stx-induced apoptosis has been induced by cleavage of poly(ADP-ribose) polymerase, release of cytochrome C and capase-3 activities with mitogen-activated protein kinases (MAPKs).…”
mentioning
confidence: 99%